Intellectual Property and Assessing its Financial Value : with a focus on life sciences - Sas, Benedikt; Vocht, Stanislas de.; Jacobs, Philippe (Oxford : Chandos Publishing, an imprint of Elsevier, 2014)
This book covers the different aspects, such as patents, trademarks and copyright of Intellectual Property (IP) from a more practical business perspective. Intellectual Property and Assessing its' Financial Value describes the differences between regions, mainly the differences between the US and EU. In addition, several tools are presented for assessing the value of new IP, which is of importance before engaging on a new project that could result in new IP or for licensing purposes. The first chapter introduces the different types of IP and illustrating the business importance of capturing an.
IP valuationIndustrial standards; Discounted cash flow methods; Valorization via a new company; Notes; References and further reading; References; Further reading; Useful websites; Appendix 1 An example of a CDA; Appendix 2 An example of an MTA; Attachment 1; Appendix 3 Invention disclosure form; Purpose; When to submit; Inventors; Format; Where to submit; Further information; Index.
Includes bibliographical references (pages 149-152) and index.
Keywords: Creative ability in business; Intellectual capital; Intellectual property -- Economic aspects